2018
DOI: 10.2174/1567205015666180613113924
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Remodeling in Primary Hippocampal Astrocytes from an Alzheimer’s Disease Mouse Model

Abstract: Our data show that in cultured astrocytes from an AD mouse model, transcriptional changes occur and are different from those reported in models mimicking later stages of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…As shown in Fig. 6a, all 14 genes followed the changes found previously in primary astrocytes 40 . A plot in Fig.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…As shown in Fig. 6a, all 14 genes followed the changes found previously in primary astrocytes 40 . A plot in Fig.…”
Section: Resultssupporting
confidence: 80%
“…This allowed us to avoid the inter-clonal heterogeneity that is a characteristic of clonal selection 4850 . Validity of this approach was efficiently demonstrated in gene expression and proteomics analyses, in which four independently generated iAstro lines for both WT and 3Tg-AD genotypes were analyzed and gave consistent results, and also demonstrated that 3Tg-iAstro retains the differences as compared with WT-iAstro found previously in primary cultures 40 .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Recently, we have generated and characterized immortalized astrocytic cell lines from hippocampi of 3xTg-AD mice, a popular and well-studied AD mouse model 27 . These lines, named WT-and 3xTg-AD immortalized astrocytes (WT-iAstro and 3Tg-iAstro) recapitulate the features of primary astrocytic cultures from 3xTg-AD mice in terms of gene profiling, protein expression and Ca 2+ signaling 27,28 . Here we used WT-iAstro and 3Tg-iAstro lines to study mitochondrial functions and their association with Ca 2+ signaling, mito-ER interaction and proteostasis.…”
Section: Introductionmentioning
confidence: 98%
“…Virtually no microglial cells have been detected in purified astroglial cultures after MACS procedure as was assessed by immunostaining with anti-Iba1 antibody (1:500, D.B.A., Segrate, Italy, Cat. 019-19741) [ 81 ].…”
Section: Methodsmentioning
confidence: 99%